Poverty : A New Perspective - Wilber, George L. (Book collections on Project MUSE., 2015)
In this collection of essays poverty is viewed not merely as an economic predicament but as a ""system with measurable properties, "" of which a low income level is only one. Affecting individuals or entire regions, many of the attributes of poverty can be seen either as causes or as effects of low income. In order for governmental and institutional attempts to have any chance of success, the system of poverty must be much better understood. Working programs directed at particular problems of the poor are examined and assessed with an account of the findings of recent research that shows how the.